Red mud-based cementitious material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611043392.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]鉴于此,本发明提出了一种赤泥基胶凝材料及其制备方法与应用,旨在解决当前技术中赤泥活化效果差、体系碱度失衡、浆料流动性不佳、材料吸水性高、力学与耐久性能薄弱、配方及工艺参数不精准等问题
本发明采用机械研磨+碱性改性+微波活化的多重协同活化机制,从根本上解决赤泥硅铝酸盐晶体结构稳定、活性组分难以激发的难题。首先,机械研磨工艺可显著细化赤泥颗粒,提升物料比表面积,暴露更多内部活性反应位点;同时在研磨过程中复配各类碱性物质,可在机械力化学效应辅助下强化碱性侵蚀作用,有效破坏赤泥表层致密晶体结构,大幅提升氧化铝、氧化硅活性组分的浸出效率,初步实现赤泥活化改性。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementitious materials technology, and more specifically, to a red mud-based cementitious material, its preparation method, and its application. Background Technology
[0002] As a pillar industry of my country's basic raw materials industry, the alumina industry generates a large amount of red mud as a byproduct during production. For every ton of alumina produced, 1.0 to 2.0 tons of red mud are generated, with annual emissions exceeding 100 million tons and accumulated stockpiles exceeding several billion tons. It is one of the largest industrial solid wastes in terms of output and lowest comprehensive utilization rate. Red mud is mostly disposed of using wet stockpiling and dry damming methods, which not only occupy large amounts of land resources and increase the storage and maintenance costs for enterprises, but also pose significant environmental safety hazards. Red mud has high porosity and a high content of soluble salt and alkali components. During long-term stockpiling, these salts and alkalis can seep into the soil and groundwater with rainwater, causing regional soil salinization and excessive alkalinity in water bodies. At the same time, stockpiling red mud easily leads to dust storms, dam failures, and other safety accidents, seriously threatening the surrounding ecological environment and human safety. Therefore, achieving efficient, large-scale, and high-value utilization of red mud resources is a core research topic for solid waste environmental disposal and the green transformation of the building materials industry.
[0003] Resource utilization of cementitious materials is one of the optimal pathways for the disposal and utilization of red mud. Red mud is rich in active cementitious oxide components such as silica, alumina, calcium oxide, and magnesium oxide, which are similar in composition to traditional cement and fly ash cementitious raw materials, possessing the inherent conditions to replace traditional mineral raw materials in the preparation of inorganic cementitious materials. Compared to low-end utilization methods such as landfilling, backfilling, and brick making, preparing red mud into engineering-usable cementitious materials can significantly increase the amount of red mud disposed of and the added value of products, while reducing problems such as limestone mining and excessive carbon emissions caused by traditional silicate cement production, thus achieving significant environmental, social, and economic benefits. In recent years, the industry has conducted extensive research on red mud-based cementitious materials. Existing technologies mainly focus on preparation processes such as single modification of red mud, single solid waste compounding, and conventional hydration curing. Red mud is activated through physical grinding, conventional high-temperature calcination, and single alkaline activation, and cementitious materials are prepared by combining a small amount of auxiliary raw materials, initially realizing the resource utilization of red mud.
[0004] However, the existing red mud-based cementitious material preparation technology has a low overall maturity, severely limiting its industrial application. This is primarily due to the inherent defects of red mud itself and the technical shortcomings of existing preparation processes and formulation systems. Firstly, after undergoing a high-temperature, strong-alkali alumina production, red mud forms a dense and stable aluminosilicate crystal network structure. This high crystal structure regularity and stable bond energy result in a large amount of silicon and aluminum active components being encapsulated within the crystal lattice. Under normal temperature and conventional modification conditions, these components are difficult to participate in the hydration and cementation reaction, leading to extremely low reactivity and poor utilization of effective cementing components. Existing conventional activation technologies rely solely on simple mechanical grinding or single-alkali activation, which can only break down the loose surface structure of red mud but cannot effectively cleave the stable aluminosilicate crystal framework. The active components inside the crystals are difficult to release, resulting in poor activation effect and low activation efficiency. Consequently, the prepared cementitious material has insufficient hydration, and its early strength and later durability fail to meet engineering standards.
[0005] Secondly, existing technologies cannot precisely control the alkalinity of the gelling system, resulting in technical challenges such as alkalinity imbalance and significant alkaline side effects. Red mud itself is highly alkaline, and most existing preparation processes directly use raw red mud for compounding without precise control and neutralization optimization of the system's alkalinity, leaving excessive free alkali in the gelling system. On the one hand, a highly alkaline environment inhibits the formation of gel products such as hydrated calcium silicate and hydrated calcium aluminate in the gelling system, disrupting the crystallization and stacking structure of hydration products, leading to decreased density and increased porosity of the gelling material. On the other hand, residual free alkali in the system easily triggers alkali-aggregate reaction, causing later-stage cracking, peeling, and strength reduction, significantly reducing the stability and service life of the gelling material. Simultaneously, some existing technologies blindly add large amounts of alkaline activators to improve activation effects, further exacerbating the problem of excessive alkalinity in the system, creating a vicious cycle of poor activation and significant alkalinity defects.
[0006] Furthermore, traditional red mud-based cementitious formulations suffer from simplistic designs and incomplete compounding systems, resulting in high water absorption, poor slurry flowability, and weak mechanical properties. Existing technologies often employ simple compounding of red mud with single-component fly ash or slag, failing to incorporate the complementary characteristics of various industrial solid waste components for refined formulation design. This leads to unreasonable particle size distribution and incomplete hydration reactions in the cementitious system. On one hand, the resulting slurry exhibits disordered internal pore structure and a high proportion of open pores, resulting in extremely high overall water absorption. During service, it is prone to moisture absorption, freeze-thaw damage, and extremely poor water resistance and frost resistance. On the other hand, high water absorption leads to abnormal viscosity, poor flowability, and insufficient water retention in the mixed slurry. This results in problems such as bleeding, segregation, and formwork blockage during construction, leading to poor construction adaptability. Moreover, the cured material exhibits numerous internal defects, with compressive and flexural mechanical properties far lower than traditional cement-based materials. Consequently, it cannot be applied to critical engineering scenarios such as main structures and roadbeds / pavements, and is limited to low-end filler materials, significantly restricting the application scope of red mud-based cementitious materials.
[0007] In addition, existing preparation processes suffer from problems such as a single activation method, a lack of auxiliary agent systems, and a crude curing regime. Traditional processes lack a targeted microwave activation and modification step, making it impossible to efficiently activate the inert components of red mud; the absence of suitable functional auxiliary agent systems such as defoamers, water-reducing agents, and water glass results in poor slurry molding quality and uncontrollable curing reaction rates; at the same time, the lack of precise parameter control over curing temperature, humidity, and curing time leads to poor stability in the curing process, large performance differences between batches of products, insufficient product consistency and reliability, and difficulty in achieving stable industrial production.
[0008] In summary, current red mud-based cementitious material preparation technologies generally suffer from numerous defects, including poor red mud activation, imbalanced system alkalinity, poor slurry fluidity, high material water absorption, weak mechanical and durability properties, and inaccurate formulation and process parameters. These defects lead to low red mud resource utilization rates, poor product performance, and insufficient engineering adaptability, severely hindering the development of the high-value utilization industry of red mud solid waste. Addressing these core pain points of existing technologies, this invention proposes a novel method for preparing red mud-based cementitious materials. Through multi-raw material compounding and modification, efficient microwave activation, precise acid-base system control, synergistic optimization of multifunctional additives, and precise curing and molding processes, this method effectively solves the shortcomings of existing technologies, significantly improves red mud activation efficiency and the overall performance of cementitious materials, and achieves efficient and high-value resource utilization of industrial solid waste. Summary of the Invention
[0009] In view of this, the present invention proposes a red mud-based cementitious material, its preparation method and application, aiming to solve the problems in the current technology such as poor red mud activation effect, system alkalinity imbalance, poor slurry fluidity, high material water absorption, weak mechanical and durability properties, and inaccurate formulation and process parameters.
[0010] This invention proposes a method for preparing a red mud-based cementitious material, comprising the following steps: Red mud is mixed and ground with alkaline substances, fly ash, slag, and carbide slag, and then transferred to a reaction vessel for microwave activation to obtain activated red mud. Activated red mud, phosphoric acid, and water are mixed and stirred. Then fly ash, slag, metakaolin, silicate cement, defoamer, water-reducing agent, and water glass are added and stirred to obtain a mixed slurry. The mixed slurry is poured into a mold and cured to obtain red mud-based cementitious material.
[0011] Preferably, the alkaline substance includes one or more of sodium carbonate, calcium carbonate, sodium hydroxide, lime, and slaked lime; The fly ash contains 40-50% silicon dioxide, 10-25% aluminum oxide, 3-10% ferric oxide, and 2-8% silicon oxide. The slag is the molten waste slag from blast furnace ironmaking, wherein the calcium oxide content is 35-45%, the silicon dioxide content is 25-35%, the aluminum oxide content is 8-18%, and the magnesium oxide content is 4-12%. The calcium hydroxide content in the carbide slag is 80-90%.
[0012] Preferably, when the alkaline substance is sodium carbonate and / or calcium carbonate, its addition amount is 5-10% of the total mass of red mud; When the alkaline substance is sodium hydroxide, its addition amount is 3-6% of the total mass of red mud; When the alkaline substance is lime and / or hydrated lime, its addition amount is 13-18% of the total mass of red mud.
[0013] Preferably, the amount of fly ash added is 20-30% of the total mass of red mud; The amount of slag added is 15-30% of the total mass of red mud; The amount of calcium carbide slag added is 20-30%; The microwave activation power is 700~800W, and the time is 20~30min.
[0014] Preferably, the phosphoric acid is a phosphoric acid solution with a concentration of 30-60 wt%; The metakaolin contains 50-55% silica and 30-40% alumina.
[0015] Preferably, the defoamer includes one or more of the following: silicone defoamer, polyether defoamer, mineral oil defoamer, and composite defoamer; The water-reducing agent includes one or more of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, aminosulfonate-based water-reducing agents, and lignosulfonate-based water-reducing agents; The water glass has a modulus of 2.2 to 3.5 and a density of 1.35 to 1.5 g / cm³. 3 .
[0016] Preferably, the ratio of activated red mud, phosphoric acid, water, fly ash, slag, metakaolin, silicate cement, and water glass is 100:20~30:10~20:10~15:15~25:20~30:30~50:10~20.
[0017] Preferably, the amount of defoamer added is 0.5-1% of the total mass of the mixed slurry; The amount of water-reducing agent added is 0.35~0.5% of the total mass of the mixed slurry.
[0018] Preferably, the curing temperature is 20~30℃, the humidity is 85~95%, and the time is 14~18 days.
[0019] The present invention also provides a red mud-based cementitious material prepared by the above preparation method.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs a multi-synergistic activation mechanism combining mechanical grinding, alkaline modification, and microwave activation to fundamentally solve the problems of stable red mud aluminosilicate crystal structure and difficulty in activating active components. Firstly, the mechanical grinding process significantly refines red mud particles, increases the specific surface area of the material, and exposes more internal active reaction sites. Simultaneously, the addition of various alkaline substances during the grinding process enhances the alkaline erosion effect under the assistance of mechanochemical effects, effectively disrupting the dense crystal structure of the red mud surface and significantly improving the leaching efficiency of alumina and silica active components, thus initially achieving the activation and modification of red mud.
[0021] This invention also introduces a microwave activation process to further modify red mud. Compared with traditional high-temperature heat conduction activation methods, microwaves can directly act on the polar molecules inside the red mud, causing the material to heat up rapidly and uniformly. This induces distortion and fracture of the stable aluminosilicate mineral lattice in the red mud, completely breaking the inert crystal framework at the microscopic level and significantly enhancing the reactivity of the silicon and aluminum active components. Simultaneously, this invention incorporates industrial solid wastes such as fly ash and slag during the microwave activation stage. These solid waste components can synergistically react with the activated red mud at low temperatures, generating low-melting-point eutectics. This achieves phase recombination and structural reconstruction under low-temperature conditions. While fully retaining the performance effects of traditional high-temperature activated materials, this invention effectively solves the problems of high energy consumption, high equipment requirements, resource waste, and high production costs associated with traditional high-temperature calcination processes. It significantly reduces the energy consumption of the red mud activation process, which is beneficial for the industrial production and application of the product.
[0022] This invention addresses the problems of existing red mud-based cementitious materials, such as single formulation, poor system compatibility, and significant performance defects. It develops a composite cementitious system synergistically adapted with activated red mud, carbide slag, phosphoric acid, metakaolin, silicate cement, and various functional additives. Each component complements the others and achieves synergistic effects. Phosphoric acid, as the core modifying component, can undergo acid-base neutralization and coordination reactions with the active components of calcium, aluminum, and silicon in activated red mud. On one hand, it precisely controls the overall alkalinity of the cementitious system, solving the problems of excessive alkalinity, easy alkali-aggregate reaction, and easy cracking and aging in traditional red mud cementitious systems. On the other hand, it generates stable calcium phosphate and aluminum phosphate cementitious products, filling the micropores of the system, significantly improving the density, structural stability, and mechanical strength of the cementitious material, and further enhancing the red mud activation effect.
[0023] The compounded calcium carbide slag in the system provides sufficient active calcium hydroxide components, providing an alkaline environment for hydration reactions and mineral phase reconstruction, adapting to traditional cementing reaction systems and ensuring basic cementing performance; metakaolin has highly active silica-alumina components, which can replenish the active raw materials of the system in a secondary manner, consume the free alkali of the system through volcanic ash reaction, optimize the micro-pore structure, and improve the durability of the material; ordinary silicate cement, as the basic cementing matrix, can ensure the early hydration rate and early strength of the material, solving the problem of low early strength of solid waste-based cementitious materials.
[0024] Meanwhile, this invention combines defoamers, water-reducing agents, and water glass to form a complete functional additive system. The water-reducing agent effectively improves the rheological properties of the mixed slurry, reduces its viscosity, enhances its fluidity and workability, and solves the problems of traditional slurries such as easy stratification, bleeding, and poor workability. The defoamer eliminates air bubbles generated during slurry mixing, reduces internal pore defects, and improves the density and mechanical properties of the cementitious material. Water glass acts as an alkaline activator and quick-setting reinforcing agent, further activating the residual inert components, accelerating the hydration and curing reaction, and improving the overall structural strength and molding stability of the cementitious material. The synergistic effect of these components solves many problems in existing technologies, such as high water absorption, poor fluidity, weak mechanical properties, and poor molding quality, significantly improving the comprehensive application performance and engineering adaptability of red mud-based cementitious materials. Detailed Implementation
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0026] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0027] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0028] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0029] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0030] This invention proposes a method for preparing a red mud-based cementitious material, comprising the following steps: Red mud is mixed and ground with alkaline substances, fly ash, slag, and carbide slag, and then transferred to a reaction vessel for microwave activation to obtain activated red mud. Activated red mud, phosphoric acid, and water are mixed and stirred. Then fly ash, slag, metakaolin, silicate cement, defoamer, water-reducing agent, and water glass are added and stirred to obtain a mixed slurry. The mixed slurry is poured into a mold and cured to obtain red mud-based cementitious material.
[0031] In this invention, the alkaline substance includes one or more of sodium carbonate, calcium carbonate, sodium hydroxide, lime, and slaked lime.
[0032] In this invention, the fly ash contains 40-50% silicon dioxide, 10-25% aluminum oxide, 3-10% ferric oxide, and 2-8% silicon oxide.
[0033] In this invention, the slag is the molten waste slag from blast furnace ironmaking, wherein the calcium oxide content is 35-45%, the silicon dioxide content is 25-35%, the aluminum oxide content is 8-18%, and the magnesium oxide content is 4-12%.
[0034] In this invention, the calcium hydroxide content in the carbide slag is 80-90%, preferably 82-88%, more preferably 84-86%, and even more preferably 85%.
[0035] In this invention, when the alkaline substance is sodium carbonate and / or calcium carbonate, its addition amount is 5-10% of the total mass of red mud, preferably 6-9%, more preferably 7-8%, and even more preferably 7.5%.
[0036] In this invention, when the alkaline substance is sodium hydroxide, its addition amount is 3-6% of the total mass of red mud, preferably 3.5-5.5%, more preferably 4-5%, and even more preferably 4.5%.
[0037] In this invention, when the alkaline substance is lime and / or hydrated lime, its addition amount is 13-18% of the total mass of red mud, preferably 14-17%, more preferably 15-16%, and even more preferably 15.5%.
[0038] In this invention, the amount of fly ash added is 20-30% of the total mass of red mud, preferably 22-28%, more preferably 24-26%, and even more preferably 25%.
[0039] In this invention, the amount of slag added is 15-30% of the total mass of red mud, preferably 18-27%, more preferably 20-25%, and even more preferably 22%.
[0040] In this invention, the amount of calcium carbide slag added is 20-30%, preferably 21-29%, more preferably 24-26%, and even more preferably 25%.
[0041] In this invention, the power of microwave activation is 700~800W and the time is 20~30min.
[0042] In this invention, the phosphoric acid is a phosphoric acid solution with a concentration of 30-60 wt%, preferably 35-55 wt%, more preferably 40-50 wt%, and even more preferably 45 wt%.
[0043] In this invention, the metakaolin contains 50-55% silica and 30-40% alumina.
[0044] In this invention, the defoamer includes one or more of the following: silicone defoamer, polyether defoamer, mineral oil defoamer, and composite defoamer; In this invention, the water-reducing agent includes one or more of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, aminosulfonate-based water-reducing agents, and lignosulfonate-based water-reducing agents.
[0045] In this invention, the water glass has a modulus of 2.2 to 3.5 and a density of 1.35 to 1.5 g / cm³. 3 .
[0046] In this invention, the ratio of activated red mud, phosphoric acid, water, fly ash, slag, metakaolin, silicate cement, and water glass is 100:20~30:10~20:10~15:15~25:20~30:30~50:10~20, preferably 100:22~28:12~18:11~14:18~22:22~28:35~45:12~18, further preferably 100:24~26:14~16:12~13:19~21:24~26:38~42:14~16, and even more preferably 100:25:15:12.5:20:25:40:15.
[0047] In this invention, the amount of defoamer added is 0.5-1% of the total mass of the mixed slurry, preferably 0.6-0.9%, more preferably 0.7-0.8%, and even more preferably 0.75%.
[0048] In this invention, the amount of water-reducing agent added is 0.35~0.5% of the total mass of the mixed slurry, preferably 0.38~0.47%, more preferably 0.40~0.45%, and even more preferably 0.42%.
[0049] In this invention, the curing temperature is 20~30℃, the humidity is 85~95%, and the time is 14~18 days.
[0050] The present invention also provides a red mud-based cementitious material prepared by the above preparation method.
[0051] Example 1 (1) Weigh 100 parts of red mud (Fe2O3 46%, Al2O3 16%, SiO2 12%, Na2O 9%, CaO 7%) by mass. Add 10 parts of alkaline substance sodium carbonate, 30 parts of fly ash, 18 parts of slag and 27 parts of carbide slag to the red mud. After mixing evenly, ball milling is carried out at a speed of 600 r / min. After ball milling for 1 h, the system temperature is raised to 62℃ and ball milling is continued for 4 h. The final system temperature is 93℃. The mixture after grinding is directly transferred to the reactor and microwave activated at a power of 700W for 25 min to obtain activated red mud.
[0052] The calcium hydroxide content in the carbide slag is 87%. Fly ash composition: SiO2 46%, Al2O3 18%, Fe2O3 7%, CaO 4%; Slag composition: CaO 38%, SiO2 29%, Al2O3 12%, MgO 6%.
[0053] 2) Weigh the materials according to the ratio of activated red mud: phosphoric acid solution: water: fly ash: slag: metakaolin: silicate cement: water glass = 100: 25: 15: 12: 20: 25: 40: 15; The phosphoric acid solution concentration was 45 wt%. Metakaolin composition: SiO2 51%, Al2O3 39%; Water glass has a modulus of 2.7 and a density of 1.44 g / cm³. 3 .
[0054] First, the activated red mud, phosphoric acid, and water are mixed evenly. Then, fly ash, slag, metakaolin, silicate cement, and water glass are added and stirred continuously. After that, 0.6% of the total mass of the mixed slurry is added as defoamer and 0.42% as water-reducing agent, and the mixture is stirred thoroughly to obtain a uniform slurry. The defoamer used is an organosilicon defoamer (BYK-028), and the water-reducing agent used is a naphthalene-based water-reducing agent (Sikament163).
[0055] 3) Curing and molding: The slurry is injected into the mold, vibrated and smoothed, and cured for 14 days in an environment with a temperature of 25℃ and a humidity of 90%. The red mud-based cementitious material is then demolded.
[0056] Example 2 (1) Weigh 100 parts of red mud (Fe2O3 35%, Al2O3 22%, SiO2 12%, Na2O 8%, CaO 6%) by mass. Add 4.5 parts of alkaline substance sodium hydroxide, 26 parts of fly ash, 24 parts of slag, and 22 parts of carbide slag to the red mud. After mixing evenly, ball milling is carried out at a speed of 550 r / min. After ball milling for 1 h, the system temperature is raised to 57℃ and ball milling is continued for 4 h. The final system temperature is 93℃. The mixture after grinding is directly transferred to the reactor and microwave activated at a power of 750W for 22 min to obtain activated red mud.
[0057] The calcium hydroxide content in the carbide slag is 85%. The composition of fly ash is as follows: SiO2 43%, Al2O3 16%, Fe2O3 8%, CaO 2%; Slag composition: CaO 44%, SiO2 27%, Al2O3 16%, MgO 10%.
[0058] 2) Weigh the materials according to the ratio of activated red mud: phosphoric acid solution: water: fly ash: slag: metakaolin: silicate cement: water glass = 100: 22: 12: 11: 18: 22: 35: 12; The phosphoric acid solution concentration was 38 wt%. Metakaolin composition: SiO2 55%, Al2O3 32%; Water glass has a modulus of 2.9 and a density of 1.39 g / cm³. 3 .
[0059] First, the activated red mud, phosphoric acid, and water are mixed evenly. Then, fly ash, slag, metakaolin, silicate cement, and water glass are added and stirred continuously. After that, 0.7% of the total mass of the mixed slurry is added as defoamer and 0.38% as water-reducing agent, and the mixture is stirred thoroughly to obtain a uniform slurry. The defoamer used is a mineral oil-based defoamer (BASF Foamaster MO2190), and the water-reducing agent used is a polycarboxylate-based water-reducing agent (Gespa ADVA 161C).
[0060] 3) Curing and molding: The slurry is injected into the mold, vibrated and smoothed, and cured for 14 days in an environment with a temperature of 25℃ and a humidity of 90%. The red mud-based cementitious material is then demolded.
[0061] Example 3 (1) Weigh 100 parts of red mud (Fe2O3 42%, Al2O3 22%, SiO2 7%, Na2O 3%, CaO 2%) by mass. Add 18 parts of alkaline substances lime, 30 parts of fly ash, 15 parts of slag and 20 parts of carbide slag to the red mud. After mixing evenly, ball milling is carried out at a speed of 600 r / min. After ball milling for 1 h, the system temperature is raised to 58℃ and ball milling is continued for 5 h. The final system temperature is 96℃. The mixture after grinding is directly transferred to the reactor and microwave activated at 800W for 30 min to obtain activated red mud.
[0062] The calcium hydroxide content in the carbide slag is 83%. Fly ash composition: SiO2 42%, Al2O3 18%, Fe2O3 9%, CaO 3%; Slag composition: CaO 38%, SiO2 27%, Al2O3 12%, MgO 9%.
[0063] 2) Weigh the materials according to the ratio of activated red mud: phosphoric acid solution: water: fly ash: slag: metakaolin: silicate cement: water glass = 100: 28: 18: 14: 22: 28: 45: 18; The phosphoric acid solution concentration was 47 wt%. Metakaolin composition: SiO2 51%, Al2O3 36%; Water glass has a modulus of 2.8 and a density of 1.46 g / cm³. 3 .
[0064] First, the activated red mud, phosphoric acid, and water are mixed evenly. Then, fly ash, slag, metakaolin, silicate cement, and water glass are added and stirred continuously. After that, 0.6-0.9% of defoamer and 0.38-0.47% of water-reducing agent by weight of the mixed slurry are added and stirred thoroughly to obtain a uniform slurry. The defoamer used is powdered defoamer (Meist P-120), and the water-reducing agent used is naphthalene-based water-reducing agent (Shandong Wanshan Chemical FDN-A).
[0065] 3) Curing and molding: The slurry is injected into the mold, vibrated and smoothed, and cured for 14 days in an environment with a temperature of 25℃ and a humidity of 90%. The red mud-based cementitious material is then demolded.
[0066] Example 4 (1) Weigh 100 parts of red mud (Fe2O3 43%, Al2O3 17%, SiO2 9%, Na2O 10%, CaO 11%) by mass. Add 18 parts of alkaline slaked lime, 25 parts of fly ash, 26 parts of slag, and 28 parts of carbide slag to the red mud. After mixing evenly, ball mill the mixture at a rate of 500 r / min. After ball milling for 1 h, the system temperature is raised to 53℃. Continue ball milling for 6 h until the final system temperature is 95℃. Transfer the mixture after grinding directly into the reactor and microwave activate it for 20 min at a power of 750 W to obtain activated red mud.
[0067] The calcium hydroxide content in the carbide slag is 85%. The composition of fly ash is as follows: SiO2 43%, Al2O3 22%, Fe2O3 7%, CaO 6%; The slag composition is as follows: CaO 38%, SiO2 25%, Al2O3 14%, MgO 9%.
[0068] 2) Weigh the materials according to the ratio of activated red mud: phosphoric acid solution: water: fly ash: slag: metakaolin: silicate cement: water glass = 100: 26: 14: 12: 21: 24: 43: 16; The phosphoric acid solution concentration was 52 wt%. Metakaolin composition: SiO2 54%, Al2O3 33%; Water glass has a modulus of 3.3 and a density of 1.48 g / cm³. 3 .
[0069] First, the activated red mud, phosphoric acid, and water are mixed evenly. Then, fly ash, slag, metakaolin, silicate cement, and water glass are added and stirred continuously. After that, 0.6-0.9% of defoamer and 0.38-0.47% of water-reducing agent by weight of the mixed slurry are added and stirred thoroughly to obtain a uniform slurry. The defoamer used is polyether defoamer (Synative RPE1720), and the water-reducing agent used is polycarboxylate high-efficiency water-reducing agent (Jiangsu Subote PCA-10).
[0070] 3) Curing and molding: The slurry is injected into the mold, vibrated and smoothed, and cured for 14 days in an environment with a temperature of 25℃ and a humidity of 90%. The red mud-based cementitious material is then demolded.
[0071] Comparative Example 1 The only difference from Example 1 is that the microwave activation step is omitted.
[0072] Comparative Example 2 The only difference from the example is the omission of phosphoric acid.
[0073] The mechanical properties of the red mud-based cementitious materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the test methods were in accordance with GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".
[0074] The test results are shown in Table 1.
[0075] Table 1. Mechanical property test results of the red mud-based cementitious materials prepared in Examples 1-4 and Comparative Examples 1-2 The water absorption rate, porosity, alkali-aggregate reaction stability, and slurry flowability of the red mud-based cementitious materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the test results are shown in Table 2. The water absorption rate, porosity, and alkali-aggregate reaction stability were tested on the 14th day of curing.
[0076] Table 2. Test results of the construction performance of the red mud-based cementitious materials prepared in Examples 1-4 and Comparative Examples 1-2 Table 1 records the compressive and flexural strength data of red mud-based cementitious materials at three core ages: 7d, 14d, and 14d after curing, under different process systems. The core comparison is with Examples 1-4 of the complete process system, Comparative Example 1 without microwave activation, and Comparative Example 2 without phosphoric acid modification. The data differences completely match the core principle of the present invention of multiple synergistic activation and precise acid-base control.
[0077] The core benefit of microwave activation to the activity and mechanical properties of red mud: Comparative Example 1 only underwent grinding and alkali mixing without microwave activation, resulting in significantly lower strength at all ages. The compressive strength at 7 days was only 17.6 MPa, the flexural strength was 2.0 MPa, the compressive strength at 14 days was 22.4 MPa, and the later strength was only 28.6 MPa. In contrast, the compressive strength of Examples 1-4 exceeded 31 MPa at each stage, reaching a maximum of 48.2 MPa in the later stages, representing a strength increase of over 68% compared to Comparative Example 1. Both early and late strength showed a significant improvement. This data confirms the core principle of the invention: traditional mechanical grinding can only break the loose surface structure of red mud, failing to cleave the stable internal aluminosilicate crystal framework, thus preventing the effective release of the encapsulated active aluminosilicate components. Microwaves of 700-800W can directly act on the polar molecules inside the material, causing lattice distortion and breakage, fully releasing the active aluminosilicate components. Combined with fly ash and slag, this achieves low-temperature synergistic mineral phase reconstruction, significantly increasing the generation of hydration products. This is the core key to solving the problems of low activity and insufficient strength in red mud.
[0078] The synergistic strengthening effect of phosphoric acid modification on strength and long-term stability: Comparative Example 2, which retained microwave activation but did not add phosphoric acid, had a 14-day compressive strength of only 28.1 MPa and a later-stage strength of 34.5 MPa, far lower than all examples. This data matches the principle of the beneficial effects of the invention: Red mud itself contains high levels of free alkali. Without phosphoric acid neutralization, the high-alkali environment inhibits the formation of gel products such as hydrated calcium silicate and hydrated calcium aluminate, resulting in poor crystallization and a loose structure of the hydration products. Phosphoric acid can undergo acid-base neutralization and coordination reactions with the active components of calcium, aluminum, and silicon in the system to generate stable dense gels of calcium phosphate and aluminum phosphate to fill the micropores. At the same time, it precisely controls the free alkali content of the system to avoid the high-alkali environment hindering the hydration reaction, thus simultaneously improving the material density and mechanical strength. It is the core modifying component for improving the upper limit of material strength and ensuring long-term mechanical stability.
[0079] The internal performance of the embodiments is stable and controllable, and suitable for industrial production: After changing different alkaline activators and adjusting the raw material ratio in Examples 1 to 4, the compressive and flexural strength fluctuations at each age are minimal. The compressive strength at 7 days is 31.7~32.2 MPa, at 14 days it is 39.6~40.6 MPa, and in the later stages it is 46.6~48.2 MPa. This shows that the formulation range of the present invention is wide and the process tolerance is good. The multi-solid waste compound system can achieve complementary advantages of components. Silicate cement ensures the early hydration rate, metakaolin continuously consumes the free alkali in the system, and the synergistic effect of multiple components allows the material strength to increase steadily and continuously without the problem of strength decay in the later stages, which fully meets the performance stability requirements of industrial-scale production.
[0080] Table 2 shows the core test indicators: water absorption rate, total porosity, alkali-aggregate reaction expansion rate, and slurry fluidity. These indicators directly verify the optimization effects of the phosphoric acid regulation system, multi-solid waste particle gradation, and multi-functional additive system on the material's construction performance and long-term durability. The data differences completely correspond to the technical innovations of this invention.
[0081] The fundamental optimization of pore structure and water resistance: Comparative Example 1, without microwave activation, had insufficient material activation and an unbalanced particle size distribution, resulting in a total porosity of 20.1% and a water absorption rate of 9.2%; Comparative Example 2, without phosphoric acid modification, had a porosity of 14.3% and a water absorption rate of 6.5%; Examples 1-4 had a total porosity of only 7.8%-8.4% and a water absorption rate reduced to 3.3%-3.5%, significantly lower than both comparative examples. This data confirms the invention principle: microwave activation fully releases the active components, and the phosphate gel generated by phosphoric acid can fill the interconnected pores inside the system. Combined with the reasonable particle size distribution of fly ash, slag, and metakaolin, the proportion of open pores in the system is significantly reduced. This fundamentally solves the industry shortcomings of traditional red mud cementitious materials, such as high porosity, high water absorption, and susceptibility to moisture and freeze-thaw damage, significantly improving the material's water resistance and freeze-thaw resistance.
[0082] A complete solution to the stability of alkali-aggregate reaction: Comparative Example 1 showed an alkali-aggregate reaction expansion rate of 0.097%, and Comparative Example 2 showed 0.062%, approaching or nearing the safety threshold for high alkali hazards; Examples 1-4 showed expansion rates of only 0.021%-0.024%, far below the national standard limit. This data matches the core innovation of the invention: phosphoric acid precisely neutralizes the free alkali inherent in red mud, and the reaction with the volcanic ash of metakaolin further consumes excess alkali components in the system, achieving precise and controllable alkalinity of the system. This completely eliminates the problems of material cracking, peeling, and strength reduction caused by the later alkali-aggregate reaction, and the long-term service stability of the material is fundamentally guaranteed.
[0083] Overall improvement in workability: Comparative Example 1 slurry flowability is only 157mm, the material is viscous and prone to bleeding and stratification; Comparative Example 2 has a flowability of 206mm in a system without phosphoric acid to adjust viscosity; Examples 1-4 have a stable flowability of 225-231mm, with excellent workability.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a red mud-based cementitious material, characterized in that, Includes the following steps: Red mud is mixed and ground with alkaline substances, fly ash, slag, and carbide slag, and then transferred to a reaction vessel for microwave activation to obtain activated red mud. Activated red mud, phosphoric acid, and water are mixed and stirred. Then fly ash, slag, metakaolin, silicate cement, defoamer, water-reducing agent, and water glass are added and stirred to obtain a mixed slurry. The mixed slurry is poured into a mold and cured to obtain red mud-based cementitious material.
2. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The alkaline substance includes one or more of sodium carbonate, calcium carbonate, sodium hydroxide, lime, and slaked lime; The fly ash contains 40-50% silicon dioxide, 10-25% aluminum oxide, 3-10% ferric oxide, and 2-8% silicon oxide. The slag is the molten waste slag from blast furnace ironmaking, wherein the calcium oxide content is 35-45%, the silicon dioxide content is 25-35%, the aluminum oxide content is 8-18%, and the magnesium oxide content is 4-12%. The calcium hydroxide content in the carbide slag is 80-90%.
3. The method for preparing a red mud-based cementitious material according to claim 2, characterized in that, When the alkaline substance is sodium carbonate and / or calcium carbonate, its addition amount is 5-10% of the total mass of red mud; When the alkaline substance is sodium hydroxide, its addition amount is 3-6% of the total mass of red mud; When the alkaline substance is lime and / or hydrated lime, its addition amount is 13-18% of the total mass of red mud.
4. The method for preparing a red mud-based cementitious material according to claim 3, characterized in that, The amount of fly ash added is 20-30% of the total mass of red mud; The amount of slag added is 15-30% of the total mass of red mud; The amount of calcium carbide slag added is 20-30%; The microwave activation power is 700~800W, and the time is 20~30min.
5. The method for preparing a red mud-based cementitious material according to claim 3, characterized in that, The phosphoric acid is a phosphoric acid solution with a concentration of 30-60 wt%; The metakaolin contains 50-55% silica and 30-40% alumina.
6. The method for preparing a red mud-based cementitious material according to claim 5, characterized in that, The defoamer includes one or more of the following: silicone defoamer, polyether defoamer, mineral oil defoamer, and composite defoamer; The water-reducing agent includes one or more of polycarboxylate water-reducing agents, naphthalene-based water-reducing agents, aminosulfonate-based water-reducing agents, and lignosulfonate-based water-reducing agents; The water glass has a modulus of 2.2 to 3.5 and a density of 1.35 to 1.5 g / cm³. 3 .
7. The method for preparing a red mud-based cementitious material according to claim 6, characterized in that, The ratio of activated red mud, phosphoric acid, water, fly ash, slag, metakaolin, silicate cement, and water glass is 100:20~30:10~20:10~15:15~25:20~30:30~50:10~20.
8. The method for preparing a red mud-based cementitious material according to claim 7, characterized in that, The amount of defoamer added is 0.5-1% of the total mass of the mixed slurry; The amount of water-reducing agent added is 0.35~0.5% of the total mass of the mixed slurry.
9. The method for preparing a red mud-based cementitious material according to claim 8, characterized in that, The curing temperature is 20~30℃, the humidity is 85~95%, and the time is 14~18 days.
10. The red mud-based cementitious material prepared by the method for preparing a red mud-based cementitious material according to any one of claims 1 to 9.